Comparision of two different andriod versions i.e Lollipop and Marshmallow, and also development of campsys mobile Andriod Application - An Overview (International Journal of Engineering and Computer Science, 2017)
In the previous system, all the information has to view in a hard file, or in website [6]. At the same time while searching any information it is too difficult to access and takes a lot of time to search the particular website. Hence, in order to overcome this problem a smart phone based application using Android can be used to make this process easier, secure and less error prone. More efficient information’s will be achieved through this system. Androidis an open source Linux based system developed by Google, and primarily aimed at mobile handsets and other portable devices. In short, we will be using them to accomplish our daily task. One application that falls into this category is the Android Application for College. This College application provides a wide range of useful information which split into several functionalities. These include: academics, news, events, facilities and all the college details. Users can install this application in their android mobile to view all of these college details and make use it.To improve mobile experience for users[17] android project aims to create successful real world products. Android is a mobile OS but it’s not limited to mobile only. It’s currently used in smart phones and televisions. There are many code name of android such as Lollipop, Kitkat, Jelly Bean, Ice cream Sandwich, Froyo, Ecliar, Donut etc. In this paper we are also discussing aboutcomparison of androidLollipop version, its features, and its issues with android Marshmallow versions and also the development of Campsys mobile application.